2023
DOI: 10.3389/fgene.2022.1004931
|View full text |Cite
|
Sign up to set email alerts
|

The association between plasma chemokines and breast cancer risk and prognosis: A mendelian randomization study

Abstract: Background: Despite the potential role of several chemokines in the migration of cytotoxic immune cells to prohibit breast cancer cell proliferation, a comprehensive view of chemokines and the risk and prognosis of breast cancer is scarce, and little is known about their causal associations.Methods: With a two-sample Mendelian randomization (MR) approach, genetic instruments associated with 30 plasma chemokines were created. Their genetic associations with breast cancer and its survival by molecular subtypes w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…These IVs act as effective proxies for observed exposures, providing more robust estimates of causality compared to traditional observational studies (Fang et al, 2024). Recent MR studies have demonstrated that SNPs related to immune cells can serve as exposure factors influencing tumor development (Bouras et al, 2022;Yu et al, 2022;Aru et al, 2023;Yin et al, 2023). However, the relationship between immune cells, metabolites, and BC has not been explored using MR.…”
Section: Introductionmentioning
confidence: 99%
“…These IVs act as effective proxies for observed exposures, providing more robust estimates of causality compared to traditional observational studies (Fang et al, 2024). Recent MR studies have demonstrated that SNPs related to immune cells can serve as exposure factors influencing tumor development (Bouras et al, 2022;Yu et al, 2022;Aru et al, 2023;Yin et al, 2023). However, the relationship between immune cells, metabolites, and BC has not been explored using MR.…”
Section: Introductionmentioning
confidence: 99%
“…This approach mitigates the confounding issues inherent in observational epidemiology, ultimately yielding more dependable and rigorous results. MR is now widely used in the study of BC 24 26 . In this study, we performed MR analysis of two samples to investigate the potential association between peripheral blood leukocyte counts and breast cancer risk.…”
Section: Introductionmentioning
confidence: 99%